Bilateral Testicular Torsion in Bilateral Polyorchidism—A Case Report - Breno Lanter Cardoso; Bruno Roberto da Silva Ferreira; Élcio Dias Silva; Anuar Ibrahim Mitre (Case Reports in Urology, 2024)
A 17-year-old patient with acute testicular pain had no blood flow observed on scrotal ultrasound Doppler on either side, suggestive of bilateral torsion. The patient underwent immediate scrotal surgical exploration, and a numerical anomaly was observed during surgery—there were two testicles on each side, and all four exhibited torsion. After detorsion, circulation was recovered, and three of four testicles were kept. One dystrophic testis was removed.